Motif Penggunaan Filter Instagram di Kalangan Perempuan Dewasa di Bandung - Zakiyah Nur Rahmah; Adi Muhammad Ramdhan (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to analyze the motives behind the use of Instagram filters among adult women in Bandung. This topic is particularly interesting to explore because the use of Instagram filters has become an addictive behavior and a perceived necessity for adult women in Bandung when presenting themselves on the platform. Many adult women in Bandung utilize Instagram filters for various purposes and objectives. This study is grounded in Alfred Schutz’s phenomenological theory and employs a qualitative research approach with a phenomenological research type. The subject selection technique used is purposive sampling, involving six participants. Data collection was conducted through interviews, observation, and document studies. The findings of this study reveal that the motives behind adult female students in Bandung using Instagram filters include: (1) entertainment, (2) aesthetics, and (3) self-image creation